2018
DOI: 10.1108/ijaim-04-2016-0045
|View full text |Cite
|
Sign up to set email alerts
|

Market reaction to the transitory effects of IFRS: an examination of disaggregated measures

Abstract: Purpose This study examines how International Financial Reporting Standards (IFRS) are applied, disaggregates the cumulative effect of the IFRS transition into magnitude measurements of the standard-to-standard differences (by standard) and management discretionary choices (by choice) and tests which transitory effects at every level of disaggregation alter investor behavior. Design/methodology/approach Using hand-collected data from the IFRS 1 disclosures, the research design consists of eight regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Hilliard and Neidermeyer (2018) found that there were market reactions on first-time adoption reconciliation adjustments. However, a standard by standard adjustment provides enhanced explanatory power to market reactions when compared with aggregate measures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hilliard and Neidermeyer (2018) found that there were market reactions on first-time adoption reconciliation adjustments. However, a standard by standard adjustment provides enhanced explanatory power to market reactions when compared with aggregate measures.…”
Section: Literature Reviewmentioning
confidence: 99%